Conversion of TrueType fonts to computerized embroidery codes - Montecastro, Samuel S. (1997)
This project is a Windows program that directly converts TrueType-formatted text to computerized embroidery stitch codes. Graph theory and expert system techniques are employed in a solution that requires minimal end-user expertise and interaction. Programmed in the Windows 95 platform through Microsoft Visual C++, the application features a simple word processor interface for user input. The CLIPS expert system tool is utilized to determine the optimum path stitching through the characters must be performed.